Remote sensing of the Earth by synthetic aperture radar - A.N. Leukhin; V.I. Bezrodnyi; A.A. Voronin (Учёные записки Казанского университета: Серия Физико-математические науки)
A synthetic aperture radar is usually a complex software and hardware system. It allows obtaining images in radio range comparable in resolution with optical systems. The advantage of radio waves is that the images are of high quality, despite cloudiness and dark time. The development of algorithms for such systems is a rather complex process. In this case, mathematical modeling i s applied in purpose to reduce costs. In this paper, an overview of the earlier created systems has been provided. We have discussed the methods for calculating the scattered electromagnetic field. We have identified the methods that are most suitable for simulating a synthetic aperture radar. Combination of different approximation methods allows to process large scenes. Various effects that arise upon the propagation of radio waves have been taken into account. We have also described the algorithms for synthesis of radar images. In particular, we have considered the range-migration and time-frequency processing algorithms. We have shown that the frequency-time processing algorithm is preferable for synthesis of radio images in the X-band due to its speed. In opposite, the range-migration effect in P-band is too strong to ignore it. The time-frequency algorithm does not give a focused image with serious artifacts. It is better to use the range-migration algorithm for P-band.